2020
DOI: 10.3390/nu12103198
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Micronutrients in Support of the Immune Response against Viral Infections

Abstract: Viral infections are a leading cause of morbidity and mortality worldwide, and the importance of public health practices including handwashing and vaccinations in reducing their spread is well established. Furthermore, it is well known that proper nutrition can help support optimal immune function, reducing the impact of infections. Several vitamins and trace elements play an important role in supporting the cells of the immune system, thus increasing the resistance to infections. Other nutrients, such as omeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
154
2
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(172 citation statements)
references
References 281 publications
(397 reference statements)
1
154
2
15
Order By: Relevance
“…VD supplementation has demonstrated efficacy in the prevention of acute respiratory infections, with the most significant results observed in patients receiving daily or weekly VD doses [5]. Moreover, different authors have demonstrated that people with VD insufficiency (25OHD < 30 ng/ml) or deficiency (25OHD < 20 ng/ml) have a higher risk of developing respiratory infections [6]. With specific regard to COVID-19, it is important to underline that the disease has mainly spread in winter when is more probable to observe VD deficiency and that the severity of COVID-19 has shown a north-south gradient, being more pronounced in latitudes associated with a deficient VD status 4 .…”
Section: Vitamin Dmentioning
confidence: 99%
See 3 more Smart Citations
“…VD supplementation has demonstrated efficacy in the prevention of acute respiratory infections, with the most significant results observed in patients receiving daily or weekly VD doses [5]. Moreover, different authors have demonstrated that people with VD insufficiency (25OHD < 30 ng/ml) or deficiency (25OHD < 20 ng/ml) have a higher risk of developing respiratory infections [6]. With specific regard to COVID-19, it is important to underline that the disease has mainly spread in winter when is more probable to observe VD deficiency and that the severity of COVID-19 has shown a north-south gradient, being more pronounced in latitudes associated with a deficient VD status 4 .…”
Section: Vitamin Dmentioning
confidence: 99%
“…Therefore, its wide-spectrum immunomodulatory action allows the hypothesis of the utility of VD supplementation in COVID-19, both for the prevention of the progression to the severe manifestations of the disease and for the reduction of the transmission of the infectious agent. Data deriving from previous studies analyzing the role of VD supplementation in the prevention and treatment of respiratory infections are markedly heterogeneous, as the baseline VD levels of the population examined and the posology of VD are not standardized [6]. However, in most of the trials on pediatric patients, the intervention consists of a daily intake of 400-1200 IU of VD [5,6,13].…”
Section: Vitamin Dmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that omega-3 polyunsaturated fatty acids (omega-3 PUFA), vitamins (folate, A, B6, B12, C, D, and E) and minerals (copper, iron, magnesium, selenium, and zinc), improve the immune system [ 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Although supplementations with omega-3 PUFA and/or micronutrients have been suggested to improve clinical outcomes of patients with ARDS [ 174 , 175 , 176 , 177 ] and to improve public health [ 167 , 177 ], it has been pointed out that only individuals at high-risk of specific nutrient deficiencies could benefit from supplementation, whereas the supplementation of a single nutrient is not promising in the general population [ 178 ]. Moreover, it has been recently found that zinc supplementation in pregnant women decreased hemoglobin concentration [ 179 ].…”
Section: Mechanisms Of the Mediterranean Diet Componentsmentioning
confidence: 99%